Програмна система для управління замовленнями та доставкою будівельних матеріалів зі складу - Шанін, Р. В.; Побіженко, І. О. (ХНУРЕ, 2025)
In the era of rapid growth wІТhin the construction industry, effective management of order processing and delivery of building materials is paramount for enhancing operational efficiency. The main goal of the research is to improve and optimize the processes of order processing and delivery of building materials from warehouses using modern information technologies. Achieving high efficiency, reducing operation time, and minimizing errors in logistical processes are key objectives of the work. In today's fast-paced construction sector, optimizing business processes is essential. The proposed solution aims to enhance the entire order lifecycle from order creation to final delivery by integrating advanced technological solutions that not only streamline software development but also significantly optimize internal business operations.
Keywords: замовлення; доставка; будівельні матеріали